Uji Kualitas Mikrobiologi Air Sungai Manjali Kecamatan Lewa Kabupaten Sumba Timur - Anita Tamu Ina; Agustinus Umbu Luwa Djongu; Sem Nggala Dehi (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The Manjali River is one of the rivers that cross Lewa District, East Sumba Regency. The Manjali River is used by local people for activities. The number of community activities around the river increases the amount of domestic waste that enters the Manjali River. This study aims to measure the microbiological quality of river water quality standards in the Manjali River. The sampling technique used in this study used purposive sampling by taking samples at 3 station points and then microbiological testing of water using the MPN method with 3 stages of testing, namely presumptive test, confirmed test, and complete test). The test results during the 2-day incubation proved that no bubbles were produced in the Durham tube, which means that there were no coliform bacteria in the Manjali River water so the water is fit for use by the community to worthy their clean water needs.